Aggtecella, a new genus of Corallinales (Rhodophyta) from the Anisian of the Aggtelek-Rudabánya Mountains, NE Hungary - Senowbari-Daryan, Baba; Velledits, Felicitász (Facies, 2007)
A description is given of the new Corallinales (Rhodophycean) alga Aggtecella hungarica from the Anisian reef limestones of the Aggtelek-Rudabánya Mountains, NE Hungary. Aggtecella is an encrusting nodular alga similar to Lithoporella melobesoides (Foslie) known from Tertiary deposits. A. hungarica occurs, in addition to the type locality (Anisian), also in the Ladinian-Carnian Wetterstein reef limestones in the Southern Alps and in Carnian reef boulders in Sicily.
UnivIS-Import:2017-11-07:Pub.2007.nat.dgeo.IGM.LP.aggtec
Keywords: Aggtecella; Alga; Anisian; Hungary; Rhodophyta; Triassic